Super and Selective Adsorption of Cationic Dyes onto Carboxylate-Modified Passion Fruit Peel Biosorbent - Chen, Kaiwei; Du, Linlin; Gao, Peng; Zheng, Junli; Liu, Yuanli; Lin, Hua (Frontiers in Chemistry, 2021)
The carboxylate-functionalized passion fruit peel (PFPCS) was an efficient and rapid biosorbent for wastewater treatment. The PFPCS exhibited excellent selectivity to the cationic dyes, where the maximum adsorption capacities for methylene blue (MB) and methyl violet (MV) were 1775.76 mg·g-1 and 3756.33 mg·g-1, respectively. And the adsorption process of MB and MV on PFPCS reached equilibrium within 20 minutes. Moreover, the adsorption conditions and mechanisms were investigated. The adsorption process was in good agreement with the pseudo-second-order and Langmuir isotherm models. And PFPCS had high reusability for the removal of MB and MV which still maintained high removal efficiency after six cycles of desorption-adsorption. Thus, PFPCS was considered as a highly efficient absorbent for removing cationic dyes from polluted water due to excellent adsorption characteristics, low cost and environmental friendliness